Supramolecular Complexation of Biological Phosphates with an Acyclic Triazolium‐Linked Anthracenyl‐1, 3‐Diconjugate of Calix[4]Arene: Synthesis, Characterization, Spectroscopy, Microscopy, and Computational Studies. Issue 44 (15th September 2014) - Sreenivasu Mummidivarapu, V. V.; Kumar Hinge, Vijaya; Samanta, Kushal; Yarramala, Deepthi S.; Pulla Rao , Chebrolu
Abstract A triazolium‐anthracenyl calix[4]arene conjugate (L) was synthesized by methylating the precursor triazole derivative and then characterized. The potential of the cationic L to differentiate nucleoside triphosphates (NTPs) from their mono‐ and diphosphates was demonstrated. Due to its unique combination of arms with the calix‐platform, a fluorescence enhancement was observed for L with all the NTPs, whereas there is no report with such enhancement being exhibited in case of all the NTPs. This has been supported by the aggregation of L observed from microscopy. Selectivity of L towards NTPs over other phosphates was a result of specific weak interactions, namely, ion–ion, hydrogen bonding and π⋅⋅⋅π, present in the 1:2 complex of L and NTPs (based on ESI MS), which were absent in their congener‐phosphates as delineated by NMR and computational studies. Thus, L stands as a unique receptor for NTPs.